Peran Guru Agama Katolik di SLB-A Karya Murni Medan - Sukma kusuma dewa; Diah ayu lestari (Damai : Jurnal Pendidikan Agama Kristen dan Filsafat, 2024)
Teaching Catholic Religious Education (CRA) classes to blind children is not easy. Qualified teachers who know how to handle children with special needs, such as the blind. The research "The Role of Catholic Religious Teachers in Special Schools (SLB-A) Karya Murni Medan was carried out with the aim of finding out the Role of Catholic Religious Teachers in Special Schools (SLB) Karya Murni Medan. religion for blind students. In this research, researchers used qualitative descriptive techniques with interview methods involving the school: the principal, two Catholic religious teachers, two Catholic religious teachers and six blind students.